2006
DOI: 10.1128/jb.188.6.2262-2274.2006
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Dehalorespiring Bacterium Desulfitobacterium hafniense Y51 and Comparison with Dehalococcoides ethenogenes 195

Abstract: Desulfitobacterium strains have the ability to dechlorinate halogenated compounds under anaerobic conditions by dehalorespiration. The complete genome of the tetrachloroethene (PCE)-dechlorinating strain Desulfitobacterium hafniense Y51 is a 5,727,534-bp circular chromosome harboring 5,060 predicted protein coding sequences. This genome contains only two reductive dehalogenase genes, a lower number than reported in most other dehalorespiring strains. More than 50 members of the dimethyl sulfoxide reductase sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
159
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 56 publications
5
159
1
1
Order By: Relevance
“…E1 was recently elucidated based on metagenome analysis of a defined co-culture [22]. The availability of OHRB genomes has allowed comparative genomic studies within genera [15,23] as well as across phyla [6]. Genome sequences of the Dehalococcoides have revealed specific metabolic requirements, including corrinoid auxotrophy for the majority of sequenced strains [13][14][15].…”
Section: Organohalide Respirationmentioning
confidence: 99%
See 2 more Smart Citations
“…E1 was recently elucidated based on metagenome analysis of a defined co-culture [22]. The availability of OHRB genomes has allowed comparative genomic studies within genera [15,23] as well as across phyla [6]. Genome sequences of the Dehalococcoides have revealed specific metabolic requirements, including corrinoid auxotrophy for the majority of sequenced strains [13][14][15].…”
Section: Organohalide Respirationmentioning
confidence: 99%
“…OHRB have been identified from diverse bacterial phyla, including the Proteobacteria, Firmicutes and Chloroflexi [5][6][7][8]. The known OHRB can be grouped as either obligate or non-obligate organohalide respirers [9].…”
Section: Organohalide Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncultured bacterium (AY945891) was previously identified from the secondary sedimentation tank of wastewater from a coking and chemical treatment plant (Shangai, China) that was studied in a denitrifying quinoline-removal bioreactor [40]. D. hafniense (AP008230) were previously isolated from an environment contaminated with dechlorinate tetrachloroethene (PCE) [41]. Suyama et al [42] observed that D. hafniense were capable of reducing either sulfate or nitrate when pyruvate was the electron donor.…”
mentioning
confidence: 99%
“…The resulting reducing equivalents allow growth using terminal electron acceptors such as fumarate (Kreher et al ., 2010; Studenik et al ., 2012). Despite the presence of several O‐demethylases encoded in the genomes of Desulfitobacterium (Nonaka et al ., 2006; Kim et al ., 2012), none of these proteins was detected in the metaproteome (Tables S3 and S6), strongly suggesting that they do not play a role in 2,4,5‐T ether cleavage.…”
Section: Discussionmentioning
confidence: 99%